Psikoedukasi Mengelola Stress Parenting Untuk Menciptakan Ketahanan Keluarga [Psychoeducation on Managing Parenting Stress to Foster Family Resilience] - Harlianty, Rully Afrita; Adhandayani, Amalia (UKInstitute, 2026)
Abstract. Parenting stress among parents with dual family career is a psychological condition that arises due to an imbalance between parenting demands and the available resources. If not properly managed, this condition may interfere with family adaptation and decrease family resilience. This community service activity aimed to provide understanding regarding the causes, impacts, and strategies for managing parenting stress. Through a seminar held at SDIT Usamah Tegal, parents were provided with information and training on adaptive strategies to cope with parenting stress. The results of the activity indicated an increase in parents’ understanding of parenting stress, which contributed to a reduction in stress levels in carrying out their parenting roles. Therefore, continuous support, provision of information, and more comprehensive stress management strategies are needed to strengthen family resilience. Abstrak. Stress parenting pada orang tua dengan peran ganda merupakan kondisi psikologis yang muncul akibat ketidakseimbangan antara tuntutan pengasuhan dan sumber daya yang dimiliki. Apabila tidak dikelola dengan baik, kondisi ini dapat mengganggu proses adaptasi keluarga dan menurunkan tingkat ketahanan keluarga. Kegiatan pengabdian masyarakat ini bertujuan untuk memberikan pemahaman mengenai faktor penyebab, dampak, serta strategi pengelolaan stress parenting. Melalui seminar yang diselenggarakan di SDIT Usamah Tegal, para orang tua memperoleh informasi dan pelatihan terkait cara mengelola stres dalam pengasuhan dengan strategi yang adaptif. Hasil kegiatan menunjukkan adanya peningkatan pemahaman orang tua mengenai stress parenting, yang berdampak pada penurunan tingkat stres dalam menjalankan peran pengasuhan. Dengan demikian, diperlukan dukungan berkelanjutan, penyediaan informasi, serta strategi pengelolaan stres yang lebih komprehensif agar ketahanan keluarga dapat terus ditingkatkan.